Coagulation and Red Cell Studies in Steady-State Subjects with Sickle Cell Anaemia and Matched AA Controls: A Study in Benin, Nigeria - Oghenefejiro, Ohwahwa; Erhamwonyi, Aghatise Kevin (International Journal of Research in Interdisciplinary Studies, 2024)
A hereditary condition known as sickle cell anemia (SCA) is characterized by vascular blockage, persistent hemolysis, and recurring episodes of discomfort. Among the major consequences that SCA patients experience are irregularities in coagulation and changes in red blood cell indices. The purpose of this study was to assess red cell parameters and coagulation in steady-state SCA participants in Benin, Nigeria, as well as matched AA controls. For the study, a total of 100 age- and sex-matched AA controls and 100 SCA patients in steady-state were enrolled. Standard laboratory procedures were used to collect and analyze blood samples for red cell indices (MCHC, hematocrit, RBC count, APTT, INR, and fibrinogen) and coagulation parameters (PT, APTT, INR, and fibrinogen). The red cell index and coagulation parameters between SCA patients and controls differed significantly, according to the results. Patients with SCA had coagulopathy as evidenced by extended PT and APTT, elevated INR, and reduced fibrinogen levels. Anemia, hypochromia, and microcytosis were found in SCA patients' red cell indices. Significant correlations between coagulation measures and red cell indices were revealed by correlation analysis. The study emphasizes how crucial it is to routinely check red cell and coagulation markers in SCA patients in order to avoid problems. The findings have implications for the care and treatment of SCA patients in Nigeria as well as for the amount of knowledge already known about the pathophysiology of the condition. The study suggests more investigation into the molecular processes that underlie the anomalies in coagulation observed in SCA.